Dynamic Relocalization of Histone Macroh2a1 from Centrosomes to Inactive X Chromosomes during X Inactivation - Rasmussen, Theodore P. (The Rockefeller University Press, 2000)
Histone variant macroH2A1 (macroH2A1) contains an NH(2)-terminal domain that is highly similar to core histone H2A and a larger COOH-terminal domain of unknown function. MacroH2A1 is expressed at similar levels in male and female embryonic stem (ES) cells and adult tissues, but a portion of total macroH2A1 protein localizes to the inactive X chromosomes (Xi) of differentiated female cells in concentrations called macrochromatin bodies. Here, we show that centrosomes of undifferentiated male and female ES cells harbor a substantial store of macroH2A1 as a nonchromatin-associated pool. Greater than 95% of centrosomes from undifferentiated ES cells contain macroH2A1. Cell fractionation experiments confirmed that macroH2A1 resides at a pericentrosomal location in close proximity to the known centrosomal proteins γ-tubulin and Skp1. Retention of macroH2A1 at centrosomes was partially labile in the presence of nocodazole suggesting that intact microtubules are necessary for accumulation of macroH2A1 at centrosomes. Upon differentiation of female ES cells, Xist RNA expression became upregulated and monoallelic as judged by fluorescent in situ hybridization, but early Xist signals lacked associated macroH2A1. Xi acquired macroH2A1 soon thereafter as indicated by the colocalization of Xist RNA and macroH2A1. Accumulation of macroH2A1 on X chromosomes occurred with a corresponding loss of centrosomal macroH2A1. Our results define a sequence for the loading of macroH2A1 on the Xi and place this event in the context of differentiation and Xist expression. Furthermore, these results suggest a role for the centrosome in the X inactivation process.